Open-label phase 3 study of intravenous golimumab in patients with polyarticular juvenile idiopathic arthritis - Ruperto, Nicolino; Brunner, Hermine; Pacheco-Tena, Cesar; Louw, Ingrid; Vega-Cornejo, Gabriel; Spindler, Alberto J.; Kingsbury, Daniel J.; Schmeling, Heinrike; Borzutzky, Arturo; Cuttica, Ruben; Inman, C. J.; Malievskiy, Victor; et al. (Oxford Univ Press, 2021)
Objectives. To assess efficacy, pharmacokinetics (PK) and safety of intravenous (i.v.) golimumab in patients with polyarticular-course JIA (pc-JIA). Methods. Children aged 2 to <18 years with active pc-JIA despite MTX therapy for >= 2months received 80 mg/m(2) golimumab at weeks 0, 4, then every 8 weeks through week 52 plus MTX weekly through week 28. The primary and major secondary endpoints were PK exposure and model-predicted steady-state area under the curve (AUC(ss)) over an 8-week dosing interval at weeks 28 and 52, respectively. JIA ACR response and safety were also assessed. Results. In total, 127 children were treated with i.v. golimumab. JIA ACR 30, 50, 70, and 90 response rates were 84%, 80%, 70% and 47%, respectively, at week 28 and were maintained through week 52. Golimumab serum concentrations and AUC(ss) were 0.40 mu g/ml and 399 mu g. day/ml at week 28. PK exposure was maintained at week 52. Steady-state trough golimumab concentrations and AUC(ss) were consistent across age categories and comparable to i.v. golimumab dosed 2mg/kg in adults with rheumatoid arthritis. Golimumab antibodies and neutralizing antibodies were detected via a highly sensitive drug-tolerant assay in 31% (39/125) and 19% (24/125) of patients, respectively. Median trough golimumab concentration was lower in antibody-positive vs antibody-negative patients. Serious infections were reported in 6% of patients, including one death due to septic shock. Conclusion. Body surface area-based dosing of i.v. golimumab was well tolerated and provided adequate PK exposure for clinical efficacy in paediatric patients with active pc-JIA.
Keywords: golimumab; intravenous; juvenile idiopathic arthritis; pharmacokinetics; tumour necrosis factor alpha